Gardening at the Margins : Convivial Labor, Community, and Resistance - Valle, Gabriel R. (Book collections on Project MUSE., 2022)
This book explores how a group of homegardeners grow food in the Santa Clara Valley to transform their social relationships, heal from past traumas, and improve their health, communities, and environments--